Enterococcus faecalis Endogenous Endophthalmitis from Valvular Endocarditis. (1st July 2013) - Barge, Sidnei; Rothwell, Renata; Varandas, Rosário; Agrelos, Luís
Abstract : We report a case of a 74-year-old female, with a mitral heart valve, who presented with pain and blurred vision in the right eye for 2 days. Her visual acuity was light perception (LP) in the right eye and 20/40 in the left eye. Slit lamp examination showed corneal edema and hypopyon, and a view of the right fundus was impossible. Echography showed vitreous condensation. One day after presentation, the patient developed acute lung edema requiring hospitalization, so she was not submitted to vitreous tap and intravitreal treatment. The cardiac and systemic evaluations revealed a mitral endocarditis secondary to Enterococcus faecalis . The patient improved systemically with treatment with gentamicin, vancomycin, and linezolid. Her visual acuity remained as no LP, and her intraocular pressure (IOP) has been controlled with brimonidine bid despite developing a total cataract with 360° posterior synechia. A cardiac source for endogenous endophthalmitis should be considered in the presence of a prosthetic cardiac valve. The treatment and followup must be made in cooperation with a cardiologist specialist, but the ophthalmologist can play a key role in the diagnosis.